The use of bisphosphonates in multiple myeloma: Recommendations of an expert panel on behalf of the European Myeloma Network - Terpos, E.; Sezer, O.; Croucher, P.I.; García-Sanz, R.; Boccadoro, M.; San Miguel, J.; Ashcroft, J.; Bladé, J.; Cavo, M.; Delforge, M.; Dimopoulos, M.-A.; Facon, T.; et al. (Annals of Oncology, 2009)
Background: Bisphosphonates (BPs) prevent, reduce, and delay multiple myeloma (MM)-related skeletal complications. Intravenous pamidronate and zoledronic acid, and oral clodronate are used for the management of MM bone disease. The purpose of this paper is to review the current evidence for the use of BPs in MM and provide European Union-specific recommendations to support the clinical practice of treating myeloma bone disease. Design and methods: An interdisciplinary, expert panel of specialists on MM and myeloma-related bone disease convened for a face-to-face meeting to review and assess the evidence and develop the recommendations. The panel reviewed and graded the evidence available from randomized clinical trials, clinical practice guidelines, and the body of published literature. Where published data were weak or unavailable, the panel used their own clinical experience to put forward recommendations based solely on their expert opinions. Results: The panel recommends the use of BPs in MM patients suffering from lytic bone disease or severe osteoporosis. Intravenous administration may be preferable; however, oral administration can be considered for patients unable to make hospital visits. Dosing should follow approved indications with adjustments if necessary. In general, BPs are well tolerated, but preventive steps should be taken to avoid renal impairment and osteonecrosis of the jaw (ONJ). The panel agrees that BPs should be given for 2 years, but this may be extended if there is evidence of active myeloma bone disease. Initial therapy of ONJ should include discontinuation of BPs until healing occurs. BPs should be restarted if there is disease progression. Conclusions: BPs are an essential component of MM therapy for minimizing skeletal morbidity. Recent retrospective data indicate that a modified dosing regimen and preventive measures can greatly reduce the incidence of ONJ. © The Author 2009. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved.
Keywords: Bisphosphonates; multiple myeloma; Osteonecrosis of the jaw; Recommendations; renal impairment